Nasal Carriage of Staphylococci in Hospital Staff at Ordu Universty Medical School Hospital and Mupirocin Resistance (Annals of Medical Research, 2021)
Aim: Renal transplantation is one of the important treatment modalities in patients with end-stage renal failure and improves the quality of life. The aim of the present study is to determine the important issues of the anesthetic management in renal transplantation.
Keywords: Renal Transplantation; Anesthesia Management.